A Pregnant Adolescent with COVID-19 and Multisystem Inflammatory Syndrome in Children - Megan E. Trostle; Tracy B. Grossman; Christina A. Penfield; Colin K. L. Phoon; Vanessa N. Raabe; Mark F. Sloane; Ashley S. Roman (Thieme Medical Publishers, Inc., 2024)
Multisystem inflammatory syndrome in children (MIS-C), a new condition related to coronavirus disease 2019 (COVID-19) in the pediatric population, was recognized by physicians in the United Kingdom in April 2020. Given those up to the age of 21 years can be affected, pregnant adolescents and young adults are susceptible. However, there is scant information on how MIS-C may affect pregnancy and whether the presentation differs in the pregnant population. We report a case of a pregnant adolescent with COVID-19 and MIS-C with a favorable outcome. This case highlights the considerations in managing a critically ill pregnant patient with a novel illness and the importance of a multidisciplinary team in coordinating care.